"No one likes that judgmental look like you are a terrorist." Sensorial encounters with the Muslim Other in Amsterdam. Issue 120 (March 2021) - Shaker, Reza; van Lanen, Sander; van Hoven, Bettina
Highlights: Muslims are one of the Others who stand outside the somatic norm. Othering is sensed, lived, and felt in/through the body. Encounters are perceived sensorially based on smell, touch, hearing, and look. The Muslim Other is (re)produced through a set of multisensorial encounters. Abstract: Often framed in the public discourse as Europe's ultimate Other, Muslims have been heftily debated and vastly problematised by politicians, pundits, and public intellectuals as unwanted immigrants, part of a bad diversity, problematic, violent, refusals of modernity, secularism, and freedom. Thinking through the body as a phenomenal lived body, we explore Othering as a set of visual, auditory, olfactory, and haptic encounters. Employing an urban ethnography on everyday lived experiences of young Muslims in Amsterdam, the paper investigates multiple modes through which Othering is sensed, lived, and felt through the body.